TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE OF PRE-SERVICE TEACHERS’ SELF-ASSESSMENT - Nurlaila, Sri Oktaviana; Anjarwati, Rosi (ELite Journal : International Journal of Education, Language and Literature, 2024)
Technological improvements in the twenty-first century have had a significant impact on the development of education today. The integration of technology into the classroom has an impact on the learning process as well as how teachers implement and improve classroom learning activities. The ability of teachers to master technology in learning can be viewed through their Technological Pedagogical and Content Knowledge (TPACK). This study aimed to find out about the pre-service teachers’ self-assessment English teachers of their TPACK. This study used a quantitative design to determine pre-service teachers’ self-assessment of the TPACK framework. A survey was undertaken to view and gather data on TPACK using self-assessment questionnaires; participants were given the questionnaire, which had four Likert scale scales, to obtain data. The subjects of this research were 47 participants of pre-service teachers in English Language Education at STKIP PGRI Jombang. The conclusion of this study is that the overall TPACK of pre-service has an average value of 2,96 with the high category.